INTEGRATION POWER SUMS OF INTEGER NUMBERS FORMULA - Hamdi, Rafid (Iraqi Journal of Science, 2024)
In this paper we fulfill to the power sums of integer numbers formula capable of integration. , in which when we make the Integration for the (r) power sums of integer numbers formula we obtain (r+1) power sums of integer numbers formula because we rearrangement the formula was writing denoted by single variable n (the greatest number we wanted find power sums to it). The formula become able to integrate when power series rewrite denoted by variable B=n (n+1) instead of single variable n, for odd power sums of integer numbers formula. also the even power sums of integer numbers formula become able to integrate ,if we rewrite it denoted by two variables A=2n+1 & B=n(n+1) allowance single variable n. farther more in this paper we advance to locate the relationship between power sums of integer numbers formula, and each of power sums of odd integer numbers formula and power sums of even integer numbers formula.